Efecto del tiempo de transporte en la calidad de la carne de cerdos faenados en rastros Municipales - García Fernández, Luis Marcelo (2021)
The present work was based on the study on the effects of transport time on the quality of the meat of pigs slaughtered in municipal slaughterhouses. Transport is a determining factor that can cause damage to the animals before reaching slaughter, which is subsequently reflected in the quality of the meat. Based on the information obtained, it is concluded that it is necessary to develop tools and protocols that minimize the biological cost of adapting animals to pre-slaughter or ante-mortem logistics and transport, the short transport time, the load density of the truck, fasting and the time spent on the floor greater than 12 hours favors muscle glycolysis and the decrease in pH, improving its quality.